Dopuszczalność małżeństwa między przysposobionym rodzeństwem. Omówienie de lege lata oraz postulaty de lege ferenda - Skłodowski, Dariusz (PRAWO i WIĘŹ, 2025)
The aim of the paper was to present the possibilities of marriage between an adopted child and a biological child of the adopter or between two children adopted by the same person. The analysis, based on the Polish legal system, highlights the differences between the different types of adoption and their effects on the possibility of marriage. The specific effects of ordered adoption on the relationship between half-siblings were also examined. The discussion focused on the impediments to marriage and the extent to which they are applicable in the case of bonds created by adoption. The analysis made it possible to draw appropriate conclusions and to present the author’s legislative proposals on the basis of European human rights.